Application of the SQ3R reading method in learning media to understand French text level B1 "Super Texte Dynamique B1" - Juliawan, Andra; Sunendar, Dadang; Hardini , Tri Indri (Proceder: Applied Linguistics, Literature, and Language Education, 2023)
Reading comprehension is one of the important components in language. This reading comprehension can be assisted by using a reading method, with the aim that the text to be read is easy to understand and quickly understood. The use of the SQ3R reading method in the application that has been made, namely Super Texte Dynamique B1, is a medium for reading French level B1 text designed using the SQ3R reading method. This application contains seven main themes, namely Sports, Health, Education, Culture, Tourism, Social and Technology. Each text is equipped with SQ3R tools. This study uses quantitative methods, and uses the SUS system. The results showed that from 10 questions given to respondents, using the System Usability Scale (SUS) formula, the results of using this application at the excelent level were 96%, indicating that this application is very good when used to help French learner to understand B1 level texts.